PERANCANGAN BUSINESS PLAN PADA BISNIS ONLINE NPG DENGAN MENGGUNAKAN LEAN CANVAS BERORIENTASI PADA ASPEK PEMASARAN DAN ANALISIS KELAYAKAN - Valencia Rachel Nabila, (2020)
NPG is local clothing label based on online business and t-shirt as its main product. NPG business concept is eco-friendly in every aspect such as product, packaging and also raise awareness through social media campaign. For now, NPG doesn't have any business plan as a fundamental of business, thus NPG need tools for analyzing business model, promotion plan, and feasibility of business. This research using tools such as lean canvas, marketing mix and calculation of net present value, payback period, profitability index and internal rate of return for 3 conditions; optimistic, best and pessimistic for the problem solving. The result for lean canvas is the business not only sell product but also stories to tell through product design and social media. Product price is Rp 145,000.00 and promotion through digital ads and influencer. Feasibility analysis shows that only 2 conditions that are feasible with each value for NPV are Rp 16,377,033 and Rp 12,425,323, PP are 5 month 20 days and 8 months 23 days, PI value are 2.9703 and 0.81122, and IRR percentage are 45.565% and 31.081%.